1974
DOI: 10.1136/jcp.27.8.652
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin in children with thalassaemia regularly transfused

Abstract: SYNOPSIS A controlled trial of continuous chelation therapy in regularly transfused children with homozygous fl-thalassaemia has been in progress at the Hospital for Sick Children since April 1966. In the sixth and seventh years of the trial the effect of this treatment on iron overload has been assessed by estimating serum ferritin levels and liver iron concentrations in both chelator-treated and control groups. When compared with non-chelated controls, results of both these estimations were invariably lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2
5

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 8 publications
2
19
2
5
Order By: Relevance
“…There was good linear correlation (R 2 >0.5) in four out of the remaining studies 17,18,23,25 but in one of them, only in patients with lower iron burden. 18 Quality limitation of the studies were sample size (only four studies had analyzed more than 100 patients), and directness (all of them analyzed a population of patients who had started iron chelation therapy and included patients with high iron burden).…”
Section: Measures Of Body Iron Load Requiring Initiation Of Iron Chelmentioning
confidence: 99%
See 1 more Smart Citation
“…There was good linear correlation (R 2 >0.5) in four out of the remaining studies 17,18,23,25 but in one of them, only in patients with lower iron burden. 18 Quality limitation of the studies were sample size (only four studies had analyzed more than 100 patients), and directness (all of them analyzed a population of patients who had started iron chelation therapy and included patients with high iron burden).…”
Section: Measures Of Body Iron Load Requiring Initiation Of Iron Chelmentioning
confidence: 99%
“…4,9,[18][19][20][21][22][23][24] Strong linear correlation (R 2 =approximately 1.0), enabling precise quantitative estimation of body iron content, was demonstrated in one study 20 but only in patients without a histological picture of liver hepatitis. There was good linear correlation (R 2 >0.5) in four out of the remaining studies 17,18,23,25 but in one of them, only in patients with lower iron burden. 18 Quality limitation of the studies were sample size (only four studies had analyzed more than 100 patients), and directness (all of them analyzed a population of patients who had started iron chelation therapy and included patients with high iron burden).…”
Section: Measures Of Body Iron Load Requiring Initiation Of Iron Chelmentioning
confidence: 99%
“…4,15 Although it is best to treat ß-thalassemia major by regular and aggressive blood transfusion so as to promote normal physical growth, avoid skeletal deformity and control morbidity from hypoxia, 15 such an aggressive transfusion program is unfortunately often complicated by iron overload, especially if not accompanied by adequate iron chelation. 16 We could not undertake such a hypertransfusion regime because of noncompliance of our patients with DF infusion. But despite the fact that our patients were undertransfused, they still had high serum ferritin levels.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity could go in lines with recent studies that showed ferritin level was not correlated well with cardiac iron. [20][21][22] In current study rate of increase of MPI, IVCT, IVRT and ET was observed to be higher up to SF of 1962µg/L, thereafter the change was slower. This observation in current study is consistent with observation made by A. Shahmohammadi et al in which there was no significant change in MPI for SF levels between less than 2000 µg/L and more 2000 µg/L.…”
Section: Discussionmentioning
confidence: 91%